PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS KETERAMPILAN PROSES DASAR PADA MATERI EKSTRAKSI DNA KELAS XII - BIMANTARI, ARY (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
Genetics is one of topics in Biology with abstract concepts. The abstract genetics concepts could be understood if there are appropriate models/media/practical activities. An alternate to help students understanding genetics concept, especially DNA, is by integrated basic process skill in the learning process. This research aimed to produce students worksheets based on basic process skill on the topic of DNA extraction which is feasible empirically. This research was designed using the 4D development model. The empirical feasibility of student worksheets obtained from student responses, with the percentage 94.67%, so it could be concluded that the student worksheets was very feasible. Key words: Student worksheet, basic process skill, DNA extraction